Performance of initial public offerings (IPOs): The case of Shariah-compliant companies - Nurwahida Yaakub; Mohamed Sherif (Islamic Economic Studies (IES), 2019)
Purpose The purpose of this paper is to examine the informational value of Shariah-compliant disclosure in the Malaysian initial public offerings (IPOs) prospectus and whether Shariah-compliant status has an impact on the IPO initial return when adopted as a signalling mechanism. Design/methodology/approach It uses data from 320 IPOs for Shariah-compliant companies listed on the Bursa Malaysia between 2004 and 2013. Findings It finds that the degree of IPO underpricing for Shariah-compliant companies is 19.97 per cent with investors earning significant returns on the first trading day. For the effect of different factors on the degree of IPO, we find that the size and type of IPO offers have a significant impact on the degree of IPO underpricing. Other economic confidence factor models fail to yield economically plausible parameter values. Originality/value The study contributes to the literature in a number of ways. It is the first to evaluate the effect of Shariah-compliance status regulation in Malaysian market, hence it provides an insight into the effectiveness of such regulation. Second, while the existing Shariah-compliant IPO studies in the same market focus on Shariah status at the date of the studies being conducted, this study uses the information around IPO time. The information that investors receive around IPO time may influence investors' decision and valuation of the IPOs in the aftermarket. Specifically, this study is different from the previous research, as it investigates whether Shariah-compliant companies would change the average degree of IPO underpricing for companies listed on Bursa Malaysia.
Keywords: G02; G12; G17; 330; IPO underpricing; Bursa Malaysia; Shariah-compliant companies